PENGEMBANGAN WEBSITE PEMBELAJARAN BERDIFERENSIASI PROSES BERBASIS GOOGLE SITES PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Deasy Fatma Arini; Mursidah Rahmah; Riksa Suci Imaniah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop a product, namely the Development of a Differentiated Process Learning Website Based on Google Sites for Elementary School Grade IV Science Learning in Chapter 6 Indonesiaku Kaya Budaya. The method used is Research and Development (R&D). This research uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) developed by Dick and Carrey. In its implementation, this research only conducts trials up to the one-to-one stage due to limited resources. The use of this website will accommodate the diverse learning styles of students, namely visual, auditory, and kinesthetic. In it, there are several features provided such as learning materials, games, and comics that can increase students' interest in learning, increase students' enthusiasm for learning to deepen their learning, and train students' independence in learning. The results of this research show that this product is very feasible to use, with an average percentage of expert assessment results of (96.3%), with subject matter experts giving (94%), media experts giving (96%), language experts giving (97%), as well as one-to-one stage tests if averaged yield (94%).